2017
DOI: 10.1038/s41598-017-04507-w
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal neural characterization of prediction error valence and surprise during reward learning in humans

Abstract: Reward learning depends on accurate reward associations with potential choices. These associations can be attained with reinforcement learning mechanisms using a reward prediction error (RPE) signal (the difference between actual and expected rewards) for updating future reward expectations. Despite an extensive body of literature on the influence of RPE on learning, little has been done to investigate the potentially separate contributions of RPE valence (positive or negative) and surprise (absolute degree of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 85 publications
(116 reference statements)
11
67
0
Order By: Relevance
“…Subsequently, to formally test for the overlap between all three RPE components and identify potential regions integrating valence and surprise either into a signed RPE representation or a linear superposition of the two signals (Fouragnan et al, ), we performed a conjunction analysis between the valence (pattern A), the surprise (pattern B) and signed RPE (pattern C) signals. We summarize our conjunction results in Figure , which revealed a major overlap between all activations associated with signed RPE and each of the other two RPE representations in the central part of the STR.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, to formally test for the overlap between all three RPE components and identify potential regions integrating valence and surprise either into a signed RPE representation or a linear superposition of the two signals (Fouragnan et al, ), we performed a conjunction analysis between the valence (pattern A), the surprise (pattern B) and signed RPE (pattern C) signals. We summarize our conjunction results in Figure , which revealed a major overlap between all activations associated with signed RPE and each of the other two RPE representations in the central part of the STR.…”
Section: Resultsmentioning
confidence: 99%
“…First, these studies have revealed two temporally specific EEG components discriminating between positive and negative RPEs peaking around 220 and 300 ms, respectively, largely consistent with the timing of the feedback‐related negativity and feedback‐related positivity ERP components (Cohen, Elger, & Ranganath, ; Hajcak, Moser, Holroyd, & Simons, ; Yeung & Sanfey, ). Additionally, the studies also revealed a late unsigned RPE component which overlaps temporally with the late valence signal (Philiastides et al, ) but appears in a largely separate and distributed neural network (Fouragnan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations